The Utility of Annual Reports: An International Study - Chang, Lucia S.; Most, Kenneth S.; Brain, Carlos W. (Journal of International Business Studies, 1983)
This article reports on a major study which is part of ongoing international research into the use and usefulness of financial statements for investment decisions. The survey reported covered 4,000 individual investors, 900 institutional investors and 900 financial analysts, in 3 countries. It was found that the 3 groups in all 3 countries revealed a strong belief in the importance of financial statements for investment decisions whether “buy” or “hold/sell.” It was also found that the individual investor group was far less homogeneous than previous research has assumed, and that cultural or social differences between countries do exist in this field.